Preparo e caracterização de membranas de matriz mista de polidimetilsiloxano com carvão ativado para separação de acetona, butanol e etanol de soluções aquosas por pervaporação. - Bruno José Arcanjo Gonçalves (2021)
Biofuels have helped to meet the growing demand for energy in society, and in this context, 1-butanol has stood out both as a fuel and as a raw material. The problem in its production is the toxicity to the cells that ferment it, along with acetone and ethanol. In this way, pervaporation is a separation process that consists of an alternative to remove butanol, acetone and ethanol from the broth, as they are formed. In this work, composite mixed matrix membranes of polydimethylsiloxane (PDMS) filled with activated carbon were prepared and characterized to separate these organic substances from synthetic aqueous solutions by pervaporation. Three types of activated carbon were evaluated as loads, and three porous materials were studied as support materials, and the adsorption of organics on activated carbon as well as the intrusion of PDMS into the pores were considered for choosing. The membranes were prepared by in-situ polymerization of the PDMS, covered by a non-woven support material. Activated carbon contents of 1, 2 and 3% by weight were used. The prepared membranes had a thickness of around 400 µm, with an estimated thickness of the selective skin around 100 µm. The results of thermal analysis indicated a small change in the observed degradation profiles, probably due to the low loading content in the membranes. No chemical changes were identified by the FTIR. Regarding pervaporation, low flux and selectivity (12 gm-2h-1, and 1.6 for the membrane with 1% CA, the best performance observed) were observed for butanol compared with similar systems in the literature. This was probably due to intrusion of PDMS into the support, producing a very thick skin and reducing performance. In addition, it was observed that the selectivity to organic substances was more dependent on the physical changes that AC caused in the arrangement of the membranes than on the chemical interactions with the permeants. The results obtained revealed the potential of the PDMS/activated carbon system for separation of butanol from dilute aqueous solutions.